Environmental impact assessment of Sadr Double - Deck Highways on the context of residential neighborhoods around - ahmad zanganeh; tajedin karami; roghayeh yadolahisaber (تحقیقات کاربردی علوم جغرافیایی)
Assessment is one of the important methods in analyzing the accomplishment of Sustainable development and as one of the necessities of planning can identify potential and actual environmental effect that is emerged as a result of the construction and development and provides logical options to solve them.  The purpose of the current research is to assess the environmental effects of multi-layer highways on the neighborhood. The research is applied In terms of purpose and descriptive in terms of nature. Moreover, this research is environment based and uses sustainable development in theory. In order to analyze the data, 8 neighborhood around the Sadr bridge (Tajrish, Gheytariyeh, Chizar, Zargandeh, Sadr, Rostam Abas, Ekhtiyarieh and Pasdaran neighborhoods) were chosen as the analyze unit. Assessment indexes were assed in term of social, skeleton, vision and health-hygiene, economic and ecologic and safety-security domains. statistical Qualitative and quantitative  methods including  one sample T test and Friedman test were used to rate the domains and spatial analysis methods (spatial statistics) were used to show the status of the neighborhood. We also used the TOPSIS technique and Iranian Leopold in order to rate the neighborhood in terms of environmental effects of multi-layer Sadr Bridge. Results of the assessment matrix showed that Sadr multi-layer project is confirmed by providing corrective options in activities with high and very high damage. Based on the research findings it was found that the neighborhoods around the Sadr multi-layer highway given the assed dimensions, each have a different susceptibility from the multi-layer Sadr Bridge. In this regard, the ecological and skeleton have the most susceptibility and the security each have the least susceptibility from the Sadr multi-layer Sadr bridge and in rating the neighborhood, Rostamabad had the most susceptibility and the Zarhandeh has the least susceptibility from the Multi-layer Sadr bridge.